Communication circuits in the press of 19th century Rio de Janeiro: webs and relationships at the initial stage - Barbosa, Marialva (Revista do Instituto Histórico e Geográfico Brasileiro, 2024)
The article addresses some aspects of communication circuits, in the initial decades of press circulation in Brazil, especially on the eve of Independence (1822), when printed newspapers began to be published gradually throughout the Brazilian territory, in what we can define as explosion of the public word from north to south of the country. The objective is to reflect on the initial moment of newspaper circulation in the 19th century, the century of the newspaper, also, in Brazil. Using the periodicals themselves as documentation to show communicational transits, it briefly highlights, based on the news published in the Diário do Rio de Janeiro, which circulated in the Court, from 1821 onwards, some of these circuits involving Brazil-Portugal.